2019
DOI: 10.3390/f10090734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post-Thinning Precipitation on Soil Acid Phosphomonoesterase Activity in Larix principis-rupprechtii Mayr. Plantations

Abstract: Soil phosphorus (P) is one of the essential macronutrients for plant growth. Phosphatase-mediated P mineralization in particular is critical for the biogeochemical cycling of P, and its activity reflects the organic P (Po) mineralization potential in soils. In recent years, global climate change has led to changes in precipitation, which inevitably has affected the P cycle as well. To study these effects of precipitation on soil acid phosphomonoesterase (AcPME) activity, the following combined thinning and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…For instance, Chen et al [24] observed that thinning treatments in Cunninghamia lanceolata plantations reduced the soil C content by lowering the availability of soil. In contrast, Tian et al [25] proposed that soil C, N, and P levels increased after thinning in Pinus massoniana plantations in China. During the development of a reforested spruce forest, the soil P content did not change significantly under thinning [26].…”
Section: Introductionmentioning
confidence: 90%
“…For instance, Chen et al [24] observed that thinning treatments in Cunninghamia lanceolata plantations reduced the soil C content by lowering the availability of soil. In contrast, Tian et al [25] proposed that soil C, N, and P levels increased after thinning in Pinus massoniana plantations in China. During the development of a reforested spruce forest, the soil P content did not change significantly under thinning [26].…”
Section: Introductionmentioning
confidence: 90%